A randomized controlled trial of routine financial toxicity screening via electronic patient-reported outcomes (AFT-39). Issue 28 (1st October 2022) - Blinder, Victoria Susana; Deal, Allison Mary; Ginos, Brenda F.; Jansen, Jennifer; Dueck, Amylou C.; Mazza, Gina L.; Henson, Sydney; Carr, Philip M; Rogak, Lauren J.; Weiss, Anna; Rapperport, Anna; Spears, Patricia; et al.
Abstract : 180 Background: Financial toxicity affects 20% of cancer survivors and is associated with decreased treatment adherence and poor clinical outcomes. No large-scale programs have been implemented to mitigate financial toxicity among patients undergoing cancer treatment. We evaluated the effect of monthly patient-reported financial toxicity screening as part of a larger digital monitoring intervention. Methods: PRO-TECT (AFT-39) is a cluster-randomized trial of patients undergoing systemic therapy for metastatic cancer. Practices were randomized 1:1 to digital symptom monitoring with patient-reported outcomes ("PRO practices") or usual care ("control practices"). Digital monitoring consisted of between-visit online or automated telephone patient surveys containing symptom, functioning, and financial toxicity screening questions for up to one year, with automated alerts sent to practice nurses for concerning survey scores. Clinical team actions in response to alerts were not mandated. The primary outcome of this analysis was development or worsening of financial difficulties, assessed via the EORTC QLQ-C30 ("Has your physical condition or medical treatment caused you financial difficulties?"), at any time compared to baseline. A randomly selected subset of patients and nurses were interviewed about their experiences with the intervention. Results: 1, 191 patients were enrolled (593 PRO; 598 control) at 52 US community oncology practices. Overall, 30.2% of patients treated at practices that received the intervention developed, or experienced worsening of, financial difficulties, compared to 39.0% of patients treated at control practices (p = 0.01). Patients and nurses interviewed stated that financial toxicity screening identified patients for financial counseling who otherwise would be reluctant to seek, or unaware of the availability of, assistance. Conclusions: Screening for financial toxicity as part of routine digital patient monitoring with PROs reduces the development, or worsening, of financial difficulties among patients undergoing systemic cancer therapy. Clinical trial information: NCT03249090.